Application of optimizing advanced encryption standard encryption algorithm in secure communication of vehicle controller area network bus - Mu, Chenzhe (Frontiers in Mechanical Engineering, 2024)
Introduction: As the main means of information exchange within vehicles, the safety of the controller area network bus directly affects the safe operation of the vehicle and the safety of passengers’ lives and property.Methods: To enhance its secure communication function, this study utilizes advanced encryption standard algorithms and improves the S-box of the algorithm to solve problems such as extended processing time. A secure communication system for the local area network bus of the vehicle controller is designed based on optimized advanced encryption standard algorithms.Results and Discussion: The results showed that when the file size was 200MB, the encryption and decryption time spent by the research method was 469.8 s and 528.5 s, respectively, which are significantly lower than traditional methods. In the simulation results, under both non-encrypted and encrypted transmission, the information remained intact throughout the entire transmission process. This indicated that the optimization algorithm effectively reduced encryption processing time and system resource consumption while ensuring data confidentiality and integrity. The new system meets the security requirements of the local area network bus of vehicle-mounted controllers.Conclusion: This study not only enhances the security of in-vehicle networks but also promotes the application and development of related encryption technologies in the field of vehicle networking. It provides strong technical support for the further development of vehicle networking and the safe operation of intelligent vehicles.